Receptor-like Kinases in Plants From Development to Defense - Tax, Frans; Kemmerling, Birgit; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Sequencing projects have revealed the presence of at least several hundred receptor kinases in a typical plant genome.  Receptor kinases are therefore the largest family of primary signal transducers in plants, and their abundance suggests an immense signaling network that we have only just begun to uncover.  Recent research findings indicate that individual receptor kinases fulfill important roles in growth and development, in the recognition of pathogens and symbionts or, in a few examples, in both growth and defense. This volume will focus on the roles of receptor kinases, their signaling pathways, and the ways in which these important signaling proteins are regulated. .
Origin, Diversity, Expansion History and Functional Evolution of the Plant Receptor-Like Kinase/Pelle Family -- Receptor Kinases in Plant Meristem Development -- The Social Network: Receptor Kinases and Cell Fate Determination in Plants -- Experimental Evidence of a Role for RLKs in Innate Immunity -- Cell-Death Control by Receptor Kinases in Arabidopsis thaliana -- Receptor Kinases Mediating Early Symbiotic Signaling -- The Cell Wall Associated Kinases, WAKs, Regulate Cell Expansion and the Stress Response -- The Regulation of Pollen-Pistil Interactions by Receptor-Like Kinases -- Receptor Kinase Interactions: Complexity of Signaling -- Ligands of RLKs and RLPs Involved in Defense and Symbiosis -- Receptor Ligands in Development -- Phosphorylation and RLK signaling -- Receptor Trafficking in Plants -- The Protein Quality Control of Plant Receptor-Like Kinases in the Endoplasmic Reticulum.
Keywords: Cell membranes .; Proteins .; Plant physiology; Cell biology; Membrane Biology; Protein-Ligand Interactions; Receptors; Plant Physiology; Cell Biology